As you like it - Shakespeare, William (Cambridge University Press, 2000)
Shakespeare's As You Like It can appear bright or somber in performance: a feast of language and a delight for comic actors; or a risk-taking exploration of gender roles. This edition offers an account of what makes the play both innocent and dangerous, mapping the complexities of its setting (a no-man's-land related to both France and England) and giving an ample commentary on its language and an analytical account of performance.